(untitled) (Homoeopathy for All, 2024)
Migraine is the sixth most disabling and the third most prevalent illness globally, affecting approximately 1 billion individuals.1 This neurological condition manifests as intense throbbing headaches often accompanied by nausea, vomiting, and sensitivity to light and sound. Such symptoms significantly impair quality of life, reducing productivity and increasing medical expenditure. In the U.S., about one in four people experiences migraines, with 18% of women, 6% of men, and 10% of children affected. In India, the prevalence of migraine is reported to be around 25% among women and 10% among men.2 Key triggers include stress, weather changes, exhaustion, certain foods and beverages, sleep disturbances, hunger, and hormonal fluctuations.3 Understanding these factors is crucial for effective management and prevention.